PROBABILITY OF CROP FAILURE DUE TO CLIMATE CHANGE, STUDY OF TOBACCO PLANT COMMODITIES IN TEMANGGUNG - Fitri Susilowati; Lilik Siswanta; Suryanto Suryanto (MESP–FEB UNS, 2018)
The objective of the study is to determine the probability of tobacco farmers experiencing crop failure as a result of climate change. The agricultural sector, includes tobacco, is a commodity that is vulnerable due to climate change. Climate change is a natural phenomenon that cannot be avoided. Symptoms of this natural phenomenon are rainfall, humidity, irradiation and temperature of floods, droughts or shifts in seasons. If these symptoms are not anticipated, the farmers have the potential to experience loss and declining in the production of copper in the temanggung, as the backbone of the economy of Central Java Province. The research method used is Qualitative Descriptive statistics with Logistic Regression. Techniques for collecting data using questionnaire techniques, interviews, observation and literature. The sample in this study amounted to 100 respondents who were tobacco farmers in the Parakan District. Based on the results of the study of independent variables that affect the probability of harvest failure of tobacco farmers in the Parakan sub-district are: (1) Age, (2) Duration of Farming, (3) Labor Wage Level, (4) Farmer Group Membership.Keywords: Adaptation, Climate Change, Logistic, Crop Failure